The Impact of Emotional Online Customer Experience On Online Consumer Behaviour In Retail Industry - Yang, Na (2016)
Customer experience has become a hot topic to marketers, practitioners and academics, and this concept has been studies in online context in many areas such as retail or service industry. In addition, e-retailers such as Amazon, some clothes retailers (H&M, Topshop) have paid more attention to the use of customer experience in online and offline condition. The understanding of online consumer behaviours has been also received much attention, but there is less focus to the impact of emotional experiential state on online shopping behaviours. Thus, this study develops and empirically tests a conceptual model which is based on Mehrabian and Russell’s PAD model of the relationship between emotional experiential state and online consumer behaviours within online shopping websites. Besides, some variables such as online customer satisfaction and repurchase intention are proposed to identify above relationship. This thesis is able to make contributions towards new concept and understanding of how emotional experiences influence online shopping behaviours. Findings in this research indicate that emotional experiential state has some impacts on online customer behaviour.